The last last-day-of-summer - Giles, Lamar. 1979- (Giles, L. R. (Lamar R.). Legendary Alston boys adventure., 2019)
"Otto and Sheed Alston are local sleuths in their zany Virginia town, masters of unraveling mischief using their unmatched powers of deduction. As summer winds down and the first day of school looms, the boys are craving just a little more time for fun, eve as they bicker over what kind of fun they want to have. That is, until a mysterious man named Mr. Flux appears with a camera that literally freezes time. Now, with the help of some very strange people and even stranger creature Otto and Sheed will have to put aside their differences to save their town--and each other. The Legendary Alston Boys have always lived in the moment, but if they don't do something fast, they may be living this moment forever."--